Infrastruktur Virtualisasi Data Center Berbasis Site Recovery Pada (PT. Informatics Oase) - Ahmad Nuril Huda; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT Informatics Oase is a subsidiary of AJB Bumiputera 1912 which carries out service contributions to customers. The development of new technology has an impact on the data center and infrastructure which becomes of increasingly high costs and is relatively certain. IT Infrastructure becomes a strategic asset that becomes a means of information anf partner relationships with customers that are needed to achieve success. But on the other hand, it is thought thaht sudden problems such as earthquakes, floods, the environment and humans can provide a real picture for companies that cause huge losses. Underlying this, planning in maintaining availability in services must be prepared accurately and thoroughly. The main solution under valid consideration has been decided that in order to replicate the existing data center with the Disaster Recovery Center (DRC) system to meet the policy objective when data center problems occur even natural disaster. This solution reference to the backup replication software to the Virtual data Center. With a direct connection to the platform the infrastructure can quickly restore to second data center to run applications for as long needed until the main data center is back online. From the results that have been implemented that the use of virtual machines with disaster recovery capabilities can provide solutions to overcome disaster recovery by using real time backup replication and failover. And safe in the event of downtime and help save costs.